The effects of exercise intensity or drafting during swimming on subsequent cycling performance in triathletes - Bentley, D. J.; Libicz, S.; Jougla, A.; Coste, O.; Manetta, J.; Chamari, K.; Millet, G. P. (Journal of Science and Medicine in Sport, 2007)
The purpose of this study was to compare the affects of drafting or a reduction of exercise intensity during swimming on the power output sustained (Pmean) during a subsequent cycle time trial (TT). In addition the relationship between peak power output (PPO) and Pmean generated during the cycle TT after swimming was examined. Nine well-trained triathletes performed an incremental cycling test to exhaustion for determination of PPO. In addition, each subject performed three swim-cycle (SC) trials consisting of 20 min cycle TT preceded by a 400 m swimming trial completed as (1) "all out" and in a non-drafting situation (SC100%); (2) at 90% of SC100% in a non-drafting situation (SC90%); (3) in a drafting position at the same controlled velocity as SC100% (SCdrafting). Swimming velocity (m s-1) was significantly (p < 0.01) lower at each time point during the 400 m swimming trial in SC90% compared with SC100% and SCdrafting. There was no significant difference in velocity between SC100% and SCdrafting. Blood lactate (BLA) concentration was also significantly (p < 0.01) lower after swimming in SC90% compared to SC100% and SCdrafting (3.8 ± 0.9 versus 7.3 ± 2.4 and 7.9 ± 2.4 mM). The Pmean was also significantly (p < 0.05) lower in SC100% relative to the SC90% and SCdrafting (226 ± 15 versus 253 ± 33 and 249 ± 36 W). There was no significant correlation between PPO (W) and Pmean for SC100% (r = -0.32), SC90% (r = 0.65; p = 0.058) or SCdrafting (r = 0.54). This study indicates that drafting or swimming at a lower velocity did not induce any conflicting affects on power output during a subsequent cycle TT. However, this study confirms that Pmean during a cycle TT is reduced when prior swimming is performed. Furthermore the positive relationship typically observed between PPO and Pmean is disrupted by swimming activity performed before a cycling TT. This factor should be considered in terms of physiological analysis of triathletes.